2013
DOI: 10.1001/jamasurg.2013.57
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiation Exposure and Cost Between Dynamic Computed Tomography and Sestamibi Scintigraphy for Preoperative Localization of Parathyroid Lesions

Abstract: Importance: Dynamic computed tomography (CT) is emerging as a first-line alternative to sestamibi scintigraphy for preoperative localization of parathyroid lesions. In recent years, there has been increased concern over the impact of radiation exposure from medical imaging, as well as on the cost of diagnostic medical procedures. An ideal diagnostic procedure would be cost effective while minimizing hazardous exposures and complication rates.Objective: To compare the radiation dose and financial cost of dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 24 publications
0
53
0
1
Order By: Relevance
“…Previous reported effective radiation doses for four phase or 4D CT have ranged from 5.56 mSv to 26.4 mSv. 6,11,19,21 These differences in radiation dose highlight the variation in protocols for parathyroid 4D CT imaging between institutions. Our results demonstrated that there was a significant reduction in the total effective radiation dose using three-phase CT scans compared with fourphase CT scans (15.9 vs 20.2 mSV, P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reported effective radiation doses for four phase or 4D CT have ranged from 5.56 mSv to 26.4 mSv. 6,11,19,21 These differences in radiation dose highlight the variation in protocols for parathyroid 4D CT imaging between institutions. Our results demonstrated that there was a significant reduction in the total effective radiation dose using three-phase CT scans compared with fourphase CT scans (15.9 vs 20.2 mSV, P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…A chest X-ray has a typical dose of 0.02 mSv. The average radiation doses in parathyroid imaging are as follows: MIBI (3.33 mSv); dynamic CT (5.56 mSv), SPECT-MIBI (7.8 mSv) (55). However, the greatest radiation dose is 4D-CT (10.4 mSv), which is the equivalent of 520 chest-X-rays (56).…”
Section: Radiation Exposurementioning
confidence: 99%
“…This discussion is beyond the scope of this article; however, effective radiation doses ranging from 5.56 to 10.4 mSv [4][5][6] have been reported, depending on the acquisition scheme used. Our second finding is that the described MR perfusion technique can successfully exploit the hypervascular nature of PTAs, a feature that can be used to differentiate them from PTA candidates such as subjacent cervical lymph node and thyroid tissue.…”
Section: Discussionmentioning
confidence: 98%
“…4D CT has shown superior accuracy compared with scintigraphy, 3 though the radiation dose remains as high as 5.56 -10.4 mSv. [4][5][6] MR imaging is an attractive alternative to both scintigraphy and 4D CT due to the lack of radiation and has been used for the evaluation of PTAs with some success, [7][8][9] though not with the same effectiveness as 4D CT. Traditional technical limitations to localizing PTAs with MR imaging have recently been addressed with modern MR imaging technology.…”
mentioning
confidence: 99%